Three‐Dimensional Super‐Branched PdCu Nanoarchitectures Exposed on Controlled Crystal Facets. Issue 1 (1st December 2016) - Iqbal, Muhammad; Li, Cuiling; Kim, Jung Ho; Alshehri, Saad M.; Nakayama, Tsuruo; Yamauchi, Yusuke
Abstract: Despite the great success of controlled synthesis of metal nanocrystals with various sizes and morphologies, an efficient one‐pot approach to preparing well‐organized three‐dimensional (3D) structures with unique facets exposed remains a great challenge. Herein, we report a unique 3D nanoarchitecture for PdCu alloy, created by a simple chemical reduction method, in which nanosized octahedral PdCu nanocrystals are directly assembled into 3D super‐branched structures. Detailed investigations of its electrocatalytic performance demonstrate that the as‐prepared facet‐controlled PdCu super‐branched nanostructures possess higher activity towards the formic acid oxidation reaction in comparison to the commercially available Pd black catalyst. Abstract : Superbranching : Three‐dimensional super‐branched PdCu nanoarchitectures exposed on controlled crystal facets were reported herein by a simple chemical reduction method.